Ignition and Combustion Characteristics of N-Butanol and FPBO/N-Butanol Blends With Addition of Ignition Improver - Wang, Yu; Han, Jinlin; Maes, Noud; Cuijpers, Michel; Somers, Bart (Frontiers in Energy Research, 2022)
In this study, the ignition and combustion characteristics of fast pyrolysis bio-oil (FPBO) are investigated in a combustion research unit (CRU), which mainly consists of a constant-volume combustion chamber. To fuel CRU with FPBO, n-butanol and 2-ethylhexyl nitrate (EHN) are used to improve the atomization and ignition properties of the fuel blends, respectively. In the first part of this study, an appropriate proportion of EHN additive into n-butanol is determined based on the balance between the ignition improvement and the amount of EHN addition. Then, the effects of FPBO content in FPBO/n-butanol blends with the same EHN addition are investigated. The effects of chamber wall temperature on the combustion are also studied. Finally, the different definitions of indicators are determined from the chamber pressure traces to quantitatively depict fuel ignition and combustion characteristics including ignition delay, combustion phasing, end of combustion and burn duration. Experimental results show that a distinct two-stage ignition process can be observed for all cases. For n-butanol with added EHN, the increase of EHN proportion could effectively advance both the low- and high-temperature reaction phases. However, this gain is obviously reduced when the percentage of EHN becomes higher than 8%. For FPBO/n-butanol blends with an addition of EHN, higher FPBO proportions have little effect on the low-temperature reaction phase, while they delay the high-temperature reaction phase. Chamber wall temperature have a significant influence on the ignition and combustion processes of the tested FPBO/n-butanol blends. With these blends, negative temperature coefficient behavior was observed in a chamber wall temperature range of 535–565 °C.